Decreased indoleamine 2, 3-dioxygenase activity and IL-10/IL-17A ratio in patients with COPD. Issue 4 (19th December 2012) - Maneechotesuwan, Kittipong; Kasetsinsombat, Kanda; Wongkajornsilp, Adisak; Barnes, Peter J
Abstract : Rationale: Indoleamine 2, 3-dioxygenase (IDO) induces generation of regulatory T cells but suppresses Th17 cells and therefore might attenuate neutrophilic inflammation. The role of IDO in neutrophilic airway diseases such as chronic obstructive pulmonary disease (COPD) remains unknown. We evaluated IDO activity and expression and interleukin (IL)-10 and IL-17A levels in sputum from patients with COPD. Methods: IDO activity and cytokine concentrations in sputum supernatants from patients with COPD of varying severity and in smoking and non-smoking control subjects were determined by high-performance liquid chromatography and ELISA, respectively. Results: Patients with COPD had reduced sputum IDO activity and expression and IL-10 levels, with increased IL-17A, IL-6 and CXCL8 concentrations and sputum neutrophils. These changes were significantly correlated with disease severity. IDO activity was decreased, but to a lesser extent, in normal smokers compared with non-smoking controls. Conclusions: Patients with COPD have a progressive reduction in IDO activity with reversal of the balance between IL-10 and IL-17A, resulting in chronic airway neutrophilic inflammation.